Investigation of and Components of the Magnetic Flux Leakage in Ferromagnetic Laminated Sample - Mustafa Göktepe (Advances in Materials Science and Engineering)
The magnetic flux leakage (MFL) technique is most commonly used for crack detection from iron bars, laminated sheets, and steel tubes of ferromagnetic nature. Magnetic flux leakage system induces a magnetic field and detects magnetic flux lines that “leak” or change because of a discontinuity in the magnetized area. An inductive coil sensor or a Hall effect sensor detects the leakage. Magnetic methods of nondestructive testing (NDT) depend on detecting this magnetic flux leakage field. The ferromagnetic specimen is magnetized by suitable methods, and flaws which break the surface or just the subsurface distort the magnetic field, causing local flux leakage fields. It is very important for industrial applications to detect cracks and flaws in metal parts of the steel bridges, power stations, military tools and structures, and so forth. In this study, the inspection of cracks in laminated sheets under longitudinal magnetization will be discussed in detail.